2012
DOI: 10.1007/s00775-011-0872-x
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt substitution supports an inner-sphere electron transfer mechanism for oxygen reduction in pea seedling amine oxidase

Abstract: Copper amine oxidases (CAOs) are a large family of proteins that use molecular oxygen to oxidize amines to aldehydes with the concomitant production of hydrogen peroxide and ammonia. CAOs utilize two cofactors for this reaction: topaquinone (TPQ) and a Cu(II) ion. Two mechanisms for oxygen reduction have been proposed for these enzymes. In one mechanism (involving inner-sphere electron transfer to O(2)), Cu(II) is reduced by TPQ, forming Cu(I), to which O(2) binds, forming a copper-superoxide complex. In an al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Lastly, the release of ammonia in the presence of water reoxidizes TPQ (Mills et al, 2012). The oxidative half-reaction uses indirect, inner-sphere electron transfer, and is demonstrated in pea seedling CuAO (Mills et al, 2012(Mills et al, , 2019.…”
Section: Copper-containing Amine Oxidases (Cuao)mentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, the release of ammonia in the presence of water reoxidizes TPQ (Mills et al, 2012). The oxidative half-reaction uses indirect, inner-sphere electron transfer, and is demonstrated in pea seedling CuAO (Mills et al, 2012(Mills et al, , 2019.…”
Section: Copper-containing Amine Oxidases (Cuao)mentioning
confidence: 99%
“…The superoxide attacks the semiquinone of the TPQ ring, and proton-coupled electron transfer results in the iminoquinone form of TPQ with release of hydrogen peroxide ( Dooley et al, 2017 ). Lastly, the release of ammonia in the presence of water re-oxidizes TPQ ( Mills et al, 2012 ). The oxidative half-reaction uses indirect, inner-sphere electron transfer, and is demonstrated in pea seedling CuAO ( Mills et al, 2012 , 2019 ).…”
Section: Mechanistic Basis Of Plant Copper Metalloenzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of the first electron transfer from cofactor to O 2 is being actively pursued, and it has been suggested that CAOs may be capable of using more than one mechanism to reduce O 2 but that each different CAO has a clear preference for either inner or outer sphere electron transfer [89,103,104]. Regardless, O 2 ultimately accepts two electrons and two protons from the cofactor, yielding H 2 O 2 and the iminoquinone (G in Scheme 4).…”
Section: Catalysis In Caosmentioning
confidence: 99%
“…In contrast to the four-coordinate tetrahedrally bound cobalt ion in Co II -apoAGAO, Co II -AGAO contains six-coordinate cobalt ligated by the three histidine residues, axial and equatorial water ligands common to the native structure and an additional water molecule in an octahedral geometry. Such geometric differences may explain the inefficiency of Co II -PSAO in catalyzing substrate oxidation in relation to native Cu II -PSAO (Mills et al, 2012). It appears that differences in metal-coordination geometry, in conjunction with additional factors such as Lewis acidity and redox potential, coordinate to determine whether a metal can initiate biogenesis as well as sustain efficient catalysis in the mature CAO.…”
Section: Figurementioning
confidence: 99%